Differences in Sole Carbon Source Utilization of the Dental Plaque Microbiota Between Caries-Free and Caries-Affected Children - Tian, Jing; Shi, Weihua; Xu, He; Wang, Guiyan; He, Xuesong; Chen, Feng; Qin, Man (Frontiers in Microbiology, 2020)
Increasing lines of evidence indicate that while microbial profile might vary, community-level metabolic potential is often more stably correlated with healthy and diseased states. Here, we investigated the community-level metabolic diversity of dental plaque microbiota from caries-free (CF) and caries-affected (CA) children by measuring their sole carbon source utilization using a Biolog assay. The dietary habits of 32 CF and 31 CA children were recorded by a questionnaire. Supragingival plaque samples were collected and inoculated into Biolog AN Microplates to assess the metabolism of sole carbon sources by plaque bacteria. The results revealed significant differences in dietary habits between CF and CA children. Meanwhile, Biolog assay showed consistently higher, albeit not statistically significant, overall metabolic activity as measured by average well color development (AWCD) value in the plaque microbiota from CA group than CF group. Most importantly, the CA group had more than twice as many core-positive carbon sources (defined as being utilized by >90% of plaque microbiota from subjects within the group) as that of the CF group (31 vs. 14), including CA group-specific, cariogenic core-positive carbon sources such as sucrose, glucose and raffinose. Furthermore, CF and CA groups could be well distinguished by cluster and principle component analyses based on the types of sole carbon sources significantly differentially utilized by the two groups. Our results indicate that plaque communities associated with caries state are more metabolically versatile than those associated with healthy state, which could contribute to differential clinical caries states. Meanwhile, Biolog could be an effective tool in revealing the community-level physiological profiles of microbiota associated with different caries states.